The Determination of Optimum Buffer Stock Intervention Rules - Edwards, R.; Hallwood, C. P. (Quarterly Journal of Economics, 1980)
It has been established for some time in the case of linear supply and demand curves that are subject to parallel stochastic shift factors that the joint welfare of trading partners measured as the sum of consumers' and producers' surpluses is increased by a reduction of price instability. This paper seeks to combine this result with information on the costs of buffer stock schemes to establish the optimum degree of price stabilization. The maximization of the partners' joint expected net benefit yields an optimum intervention price range that will vary with demand and supply elasticities, and other market conditions.